Behavioural and Psychiatric Phenotypes in Men and Boys with X-Linked Ichthyosis: Evidence from a Worldwide Online Survey. - Sohini Chatterjee; Trevor Humby; William Davies (PLoS ONE)
Background X-linked ichthyosis (XLI) is a rare dermatological condition arising from deficiency for the enzyme steroid sulfatase (STS). Preliminary evidence in boys with XLI, and animal model studies, suggests that individuals lacking STS are at increased risk of developmental disorders and associated traits. However, the behavioural profile of children with XLI is poorly-characterised, and the behavioural profile of adults with XLI has not yet been documented at all. Materials and methods Using an online survey, advertised worldwide, we collected detailed self- or parent-reported information on behaviour in adult (n = 58) and younger (≤18yrs, n = 24) males with XLI for comparison to data from their non-affected brothers, and age/gender-matched previously-published normative data. The survey comprised demographic and background information (including any prior clinical diagnoses) and validated questionnaires assaying phenotypes of particular interest (Adult ADHD Self-Report Scale v1.1, Barrett Impulsiveness Scale-11, adult and adolescent Autism Quotient, Kessler Psychological Distress Scales, and Disruptive Behaviour Disorder Rating Scale). Results Individuals with XLI generally exhibited normal sensory function. Boys with XLI were at increased risk of developmental disorder, whilst adults with the condition were at increased risk of both developmental and mood disorders. Both adult and younger XLI groups scored significantly more highly than male general population norms on measures of inattention, impulsivity, autism-related traits, psychological distress and disruptive behavioural traits. Conclusions These findings indicate that both adult and younger males with XLI exhibit personality profiles that are distinct from those of males within the general population, and suggest that individuals with XLI may be at heightened risk of psychopathology. The data are consistent with the notion that STS is important in neurodevelopment and ongoing brain function, and with previous work suggesting high rates of developmental disorders in boys with XLI. Our results suggest that individuals with XLI may require medical care from multidisciplinary teams, and should help to inform genetic counselling for the condition.